From capital to welfare: Exploring how good governance mediates the impact of intellectual and social capital in border communities - Arthana, I Komang; Nursiani , Ni Putu; Riwu, Yonas Ferdinand (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to determine the role of effective governance as a mediating variable in the relationship between intellectual capital and social capital to improve community welfare in border villages, especially in Belu Regency, Indonesia. Methodology: This study uses a quantitative approach and Partial Least Squares (PLS) analysis method. Data from 155 families in border areas was collected with a survey from 28 border villages in Belu Regency that have distinctive socio-cultural characteristics. Results: Effective governance has been proven to mediate the relationship between intellectual capital and community welfare. Meanwhile, in the relationship between social capital and welfare, partial mediation was found. The distribution of well-managed village funds improves welfare, even with limited intellectual capital. Conclusions: Good governance encourages the compliance of village fund managers with the rules. Strong social capital and local customs-based also strengthen the impact of fund management on welfare. Limitations: The findings are contextual in certain villages in Belu, so they cannot be generalized. This research emphasizes the importance of strengthening governance and integrating traditional values in village resource management. Contribution: This research contributes to the literature by integrating intellectual capital, social capital, and governance into a single framework, highlighting how governance mediates development outcomes in marginalized border communities.